2010
DOI: 10.1186/1471-2334-10-267
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for and outcome of treatment of latent tuberculosis infection in a cohort of HIV-infected people in Spain

Abstract: BackgroundPrevious studies have demonstrated the efficacy of treatment for latent tuberculosis infection (TLTBI) in persons infected with the human immunodeficiency virus, but few studies have investigated the operational aspects of implementing TLTBI in the co-infected population.The study objectives were to describe eligibility for TLTBI as well as treatment prescription, initiation and completion in an HIV-infected Spanish cohort and to investigate factors associated with treatment completion.MethodsSubject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
0
19
0
3
Order By: Relevance
“…While about half (55%) of persons initiating therapy completed, only about a quarter (26%) even initiated therapy by picking up the first month’s supply of pills. The initiation rate in our study is notably less than the 91% LTBI therapy initiation rate seen in a cohort of patients presenting to TB clinic at Boston Medical Center [12], 58% initiation rate in a population of health care workers in Toronto [19], and 67% initiation rate in a cohort of HIV-infected patients in Spain [20]. Differences in initiation rates between our study and others may be attributable to different clinic populations, healthcare systems, and the fact that our study, as a program evaluation, included all persons prescribed LTBI treatment without selection bias.…”
Section: Discussionmentioning
confidence: 68%
“…While about half (55%) of persons initiating therapy completed, only about a quarter (26%) even initiated therapy by picking up the first month’s supply of pills. The initiation rate in our study is notably less than the 91% LTBI therapy initiation rate seen in a cohort of patients presenting to TB clinic at Boston Medical Center [12], 58% initiation rate in a population of health care workers in Toronto [19], and 67% initiation rate in a cohort of HIV-infected patients in Spain [20]. Differences in initiation rates between our study and others may be attributable to different clinic populations, healthcare systems, and the fact that our study, as a program evaluation, included all persons prescribed LTBI treatment without selection bias.…”
Section: Discussionmentioning
confidence: 68%
“…Em ambas as situações, as características psicossociais dos pacientes eram relacionadas ao desfecho e alguns médicos não prescreviam o tratamento da ILTB por acreditarem que o paciente não mostraria adesão a ele ou se negaria a fazê-lo. 2 Embora alguns fatores psicossociais ou demográficos dos indivíduos possam estar relacionados à não indicação da quimioprofilaxia, a ausência de prescrição e/ou realização da prova tuberculínica -amplamente recomendada -parece ser o principal fator relacionado à não indicação de tratamento da ILTB na região de Blumenau-SC, conforme nossos dados. Percebe-se que, no estudo em tela, uma maior parcela dos pacientes do sexo masculino recebe indicação para realização da PT.…”
Section: Métodosunclassified
“…Alguns estudos revelam que mais de 40,0% dos pacientes sem adesão não comparecem à primeira consulta de seguimento. 2,15 Como a quimioprofilaxia é um regime autoadministrado, isso pode acarretar um maior número de pacientes que deixarão de completar o esquema preconizado. Estudo realizado na Inglaterra comparou dois regimes com diferentes durações, quanto à adesão, e constatou que a possibilidade de escolha do paciente entre aqueles dois regimes estava diretamente relacionada à correta administração da droga.…”
unclassified
“…A recent Cochrane review found that treatment of latent M. tuberculosis infection (LTBI) in HIV-infected persons with a positive tuberculin skin test prevents tuberculosis and improves survival [4]. However, acceptance and completion of isoniazid (INH) preventive therapy is low in both HIV-uninfected and HIV-infected persons [5, 6]. The World Health Organization (WHO) recommends screening all persons with HIV for four symptoms: current cough, fever, weight loss, and night sweats.…”
Section: Introductionmentioning
confidence: 99%
“…Completion rates of INH are lower than with shorter regimens [5, 6, 810]. Given this, several recent studies have examined possible alternative regimens for the treatment of LTBI, evaluating the optimal duration of therapy, tolerability, efficacy, durability of protective effect, and cost.…”
Section: Introductionmentioning
confidence: 99%